Pengaruh Perluasan Merek Terhadap Citra Merek Pada Produk Citra Di Surabaya Selatan - Nuraini, Dewi (Equilibrium: Jurnal Ekonomi-Manajemen-Akuntansi, 2011)
Brand extension is one of the brand strategy that uses an existing brand name to enter the market with a new category. Citra is one of the brand that is expanding the brand using brand extension strategy. Citra beauty skin care products Hand and Body Lotion that has long existed, now expanded with the launch of new products with bath soap category (either solid or liquid soap), Body Scrub, facial cleansers, and facial moisturizer. From the analysis, obtained by the formula equation Y = 3.054 + 0.147 X1 + 0.179 X2-0.182 X3 + 0.133 X4 + ei by R square value of 0.261, it means that the proportion of independent variables affect the dependent variables by 26.1%, while the rest is influenced by other variables outside of this study, at 73.9%. The results say that brand extension variables simultaneously, namely: similarity, reputation, perceived risk, and innovativeness significantly affects the brand image can be proven true. By parsial similarity, reputation, perceived risk and innovativeness significantly affects the brand image. Partial coefficient of determination values for reputation (X2) is equal to 0.108 indicates that reputation is owned by the parent brand (reputation) is the dominant variable in this study.